Peer feedback of reading aloud to improve speaking fluency - Aquino Rojas, Marco Antonio (2021)
Students in a public higher institution had problems with their speaking skills specifically in their fluency. This study proposed the application of peer feedback to help students overcome their limitations in speaking. There were 51 participants. They were assigned to the experimental (N=27) and control group (N=24). Data was collected through quantitative (pre and posttests, a Likert scale survey, and a checklist) and qualitative instruments (learning logs and field notes). Quantitative results indicate that the experimental group outperformed the control group in the posttest. The pvalue indicated that the data is statistically significant meaning that the application of peer feedback of students recording (of their reading out loud) impacts students’ fluency. Cohen’s d= 1.04 confirms a large impact of the strategy for learning. Theanalysis by components of the rubric reiterates that fluency was the item that increased the most.These results were confirmed by students’ opinion about peer feedback. Qualitative data revealed there were some limitations though. Some that were mentioned were: students’ limitations in using the language, and their lack of vocabulary knowledge. Other EFL teachers may be interested in reading this thesis to improve their students’ fluency or other aspects of speaking.